2012
DOI: 10.11646/zootaxa.3503.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Additions to the taxonomy of the armadillo ants (Hymenoptera, Formicidae, Tatuidris)

DAVID A. DONOSO

Abstract: The taxonomy of the rare ant genus Tatuidris is revised by studying morphological variability among 118 specimens from 52 collection events in 11 countries, and sequences of Cytochrome Oxidase 1 (CO1 ‘DNA barcodes’) of 28 specimens from 13 localities in 6 countries. Tatuidris are cryptic ants that inhabit the leaf litter of Neotropical forests from Mexico to French Guiana, central Brazil, and Peru. Based on the extent of the morphological variability encountered throughout this broad geographic range, T. kapas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…The Neotropical genus Tatuidris was recently revised in a study that included COI DNA barcodes from the ACG (Donoso 2012). Donoso reported deep variability within this single species and 37% of this surprising variation was explained by geographic separation.…”
Section: Tatuidrismentioning
confidence: 99%
See 1 more Smart Citation
“…The Neotropical genus Tatuidris was recently revised in a study that included COI DNA barcodes from the ACG (Donoso 2012). Donoso reported deep variability within this single species and 37% of this surprising variation was explained by geographic separation.…”
Section: Tatuidrismentioning
confidence: 99%
“…Donoso reported deep variability within this single species and 37% of this surprising variation was explained by geographic separation. He concluded that this was most parsimoniously explained as T. tatusia being an allopatrically distributed single species that is undergoing isolation by distance (Donoso 2012). Pringle et al (2012) surveyed Azteca across the Neotropics and their study included samples taken from within the ACG.…”
Section: Tatuidrismentioning
confidence: 99%
“…Ants of the genus Tatuidris Brown and Kempf (Formicidae: Agroecomyrmecinae) are rare inhabitants of soil and leaf-litter layers of Neotropical forests from Mexico to French Guiana, central Brazil, and Peru (Donoso 2012; Lacau et al 2012). In his recent revision of the genus, Donoso (2012) considers the genus Tatuidris as monotypic, and he synonymized the recently described T. kapasi Lacau and Groc, 2012, from French Guiana, under T. tatusia (first described by Brown and Kempf, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…In his recent revision of the genus, Donoso (2012) considers the genus Tatuidris as monotypic, and he synonymized the recently described T. kapasi Lacau and Groc, 2012, from French Guiana, under T. tatusia (first described by Brown and Kempf, 1968). …”
Section: Introductionmentioning
confidence: 99%
“…These are often problematic since they can be highly variable within species and prone to geographic variability, such as shown for the Neotropical Tatuidris Brown & Kempf (Donoso 2012), Malagasy Tetramorium Mayr (Hita Garcia and Fisher 2011) and Malagasy Crematogaster Lund (Blaimer 2012). Against the background of a resilient taxonomic impediment with continuously declining taxonomic resources and funding (e.g.…”
Section: Discussionmentioning
confidence: 99%